The Competitive and Combining Effects of Grain Boundary and Fe/Mo Antisite Defects on the Low‐Field Magnetoresistance in Sr2FeMoO6. Issue 4 (19th December 2013) - Wang, Jin‐Feng; Li, Zheng; Xu, Xi‐Jun; Gu, Zheng‐Bin; Yuan, Guo‐Liang; Zhang, Shan‐Tao; French, R.
<x xml:space="preserve">Abstract</x> Sr2FeMoO6 ceramics with different Fe/Mo antisite defect (ASD) concentrations and grain‐boundary (GB) properties were prepared. The competitive and combining effects of GB and Fe/Mo ASD on the transport and magnetoresistance were discussed. The GB properties, that is, intergrain coupling strength, positively related with resistivity value, is extremely sensitive to the total flux of reducing gas, in general, lower total gas flux leads to larger resistivity, thus stronger intergrain coupling strength, and then the contributions of GB effect to low‐field magnetoresistance (LFMR) increase appreciably regardless of the amount of ASD. In detail, when ASD concentration is less than 26%, LFMR is dominantly controlled by the GB effect. However, the suppressed ASD effect on LFMR behavior comes to play when the ASD content is larger than or equal to 26%, where the GB and ASD effects contribute together to the LFMR.